Crustal structure, gravity anomalies and subsidence history of the Parnaíba cratonic basin, Northeast Brazil - Tozer, B; Watts, A; Daly, M (American Geophysical Union, 2017)
Cratonic basins cover more than 10% of Earth's continental surface area, yet their origin remains enigmatic. Here, we use a 1400 km long, deep (20 s TWTT) seismic reflection profile, five wide-angle split-spread receiver gathers, gravity anomaly and well data to constrain the origin of the Parnaíba basin, a cratonic basin in Northeast Brazil. In the centre of the basin, the depth to pre-Paleozoic basement is ~3.3 km, a zone of Mid-Crustal Reflectivity (MCR) can be traced laterally for ~250 km at depths between 17-25 km and Moho depth is ~42±2 km. Gravity and P-wave modelling suggests that the MCR represents the upper surface of a high density (2985 kg m-3) and Vp (6.75–7.0 km s-1) lower crustal body, likely of magmatic origin. Backstripping of well data show a concave up decreasing tectonic subsidence, similar in form to that observed in rift-type basins. We show, however, that our seismic and gravity data are inconsistent with an extensional origin. Other basin forming mechanisms are therefore required. We show that an intrusive body in the lower crust that has loaded and flexed the surface of the crust, combined with sediment loading, provides a satisfactory fit to the observed gravity anomaly. A buried load model is consistent with seismic data, which suggest that Moho is as deep or deeper beneath the basin centre than its flanks and accounts for at least part of the exponentially decreasing tectonic subsidence through a viscoelastic stress relaxation that occurs in the lithosphere following load emplacement.